Analyses of fin ray types to detect strontium markers in juvenile blunt-snout bream Megalobrama amblycephala - Zhu, Yahua; Jiang, Tao; Chen, Xiubao; Liu, Hongbo; Phelps, Quinton; Yang, Jian (Ecological processes, 2024)
Background Restocking by introducing hatchery-reared fish into wild habitats aids in the restoration of fishery aquatic ecosystems and reefs to increase the abundance of fish resources, restore the ecological balance of water bodies, and enhance ecosystem functioning. Accurately, rapidly, and effectively evaluating the success of restocking using chemical markers (e.g., strontium [Sr]) remains challenging for fisheries management. Consequently, for non-lethal fish sampling, hard tissues, such as fin rays, have received increasing attention as a target for marking method. However, data on the differences in marking different types of fin rays remain limited. Therefore, we exposed juvenile blunt snout bream individuals ( Megalobrama amblycephala ) to 0 (control group) or 800 mg/L of SrCl 2 ·6H 2 O (marked group) for 5 days and transferred them into normal aerated water for post-immersion culture. We sampled their pectoral, dorsal, ventral, anal, and caudal fin rays. The Sr marks among the fin types were sampled at 0 and 20 days post-immersion and evaluated using an electron probe micro-analyzer (EPMA) for the five-day Sr/Ca ratios, along with line transect and Sr mapping analyses. Results Sr marking signatures were observed in all fin types in the marked group, with a success rate of up to 100%. Although marking efficiency varied among the different fin ray types, the highest Sr/Ca ratios were most often detected in the dorsal fin. Cross-sectional Sr concentration maps of all fin rays sampled showed high-Sr domains in the marked group; in contrast, the entire cross-sections of the control group displayed low Sr contents, indicating successful marking efficiency. Conclusions Fin ray Sr marking is a successful method for juvenile M. amblycephala , with the advantages of non-lethality and negligible sampling injuries, facilitating the rapid and effective evaluation of Sr marking in restocking M. amblycephala .